Lipid Microenvironment Modulates the Pore-Forming Ability of Polymyxin B - Anastasiia A. Zakharova; Svetlana S. Efimova; Olga S. Ostroumova (MDPI AG, 2022)
The ability of polymyxin B, an antibiotic used to treat infections caused by multidrug-resistant Gram-negative bacteria as a last-line therapeutic option, to form ion pores in model membranes composed of various phospholipids and lipopolysaccharides was studied. Our data demonstrate that polymyxin B predominantly interacts with negatively charged lipids. Susceptibility decreases as follows: Kdo2-Lipid A >> DOPG ≈ DOPS >> DPhPG ≈ TOCL ≈ Lipid A. The dimer and hexamer of polymyxin B are involved in the pore formation in DOPG(DOPS)- and Kdo2-Lipid A-enriched bilayers, respectively. The pore-forming ability of polymyxin B significantly depends on the shape of membrane lipids, which indicates that the antibiotic produces toroidal lipopeptide-lipid pores. Small amphiphilic molecules diminishing the membrane dipole potential and inducing positive curvature stress were shown to be agonists of pore formation by polymyxin B and might be used to develop innovative lipopeptide-based formulations.